The Implementation of Project-Based Learning Model through ORAI in Recount Material to Enhance English Speaking Skill - Kuswahyuningsih, Kuswahyuningsih; Giyoto, Giyoto; Untari, Lilik; Bustany, Zainuddin (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
The study objectives are to recognize the application of Project-based Learning (PBL) and utilization of ORAI, which can develop student’s speaking skills and immensity of the progress in recount text for tenth grade in science class 1 at MAN Sukoharjo. The students were in the second semester in Academic Year 2018/2019. More than 40 % students of tenth grade in science class 1 at MAN Sukoharjo encountered obstacles in English learning, especially in conveying recount. The data collection techniques in this research were document collection, observation, interview, and test. The data validity of this study used the triangulation method, which means that there were more techniques and observations of treatment in collecting the data. The finding reveals that the application of PBL and utilization of ORAI can improve student’s speaking skills especially in conveying recount. The average of students’ scores is found to be significantly different from each cycle. The pre-treatment average score is 69.33, the first cycle score is 72.66, and the second cycle score is 77.33. It means that almost all students can reach KKM (minimum completeness criteria). In conclusion, PBL and ORAI can be applied to enhance students’ speaking skills.